Comoros Urbanization Review : Reimagining Urbanization in Comoros - World Bank (World Bank, Washington, DC, 2021)
Through the development of informed policies and targeted investments, the objective of this Comoros urbanization review is to provide analytical support to improve the living conditions of Comoros’ urban population, especially the poor living in informal settlements and hazard prone areas. The review further buttresses the implementation of the national development strategy national accelerated growth and sustainable development strategy (SCA2D) 2018-2021 and Comoros emerging plan 2030. In its essence, it focuses on a set of foundations and variables considered necessary for Comoros to raise the standard and quality of urban life and its environment, as well as strengthen models of local governance while advancing an agenda of urban resilience. The report recommends an opportunistic posture in working towards clarifying property rights based on common principles to set the stage for a more ambitious land reform.